Professional'nyi sport i zakon - Antipov, A. F.; Ulovistova, N. V. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The legislation of the Russian Federation including the norms of the constitutional, civil, labour and international law. It is closely connected to the legislation on an education, on the social protection of the population, on the public health services, on the enterprise activity, on the privatization, on the local self-management. The significant part of the legislation on physical culture and sports coincides with the legal area of the civil legislation. However, civil-law relations have not ripened in the society yet. It is especially appreciable in that part of the Federal law, which regulates the professional sports. It would be desirable, that this problem, together with other problems of the legislation about physical culture and sports became the point of issue of the Russian sports public and experts on the law. The socio-economic conditions for this purpose are already have developed.